Reunion at IPiCEX 2014 - Chan, Margaret (Universiti Teknologi MARA, Sarawak, 2015)
At the 4th International Plantation Industry Conference and Exhibition held from 24th to 25th September 2014, I met some of my former students of the Professional Qualification Examination in Plantation Industry Management who were the pioneer students from Sarawak. They are testimonies of the success of the International Institute of Plantation Management (IIPM), a professional body founded in May 2006 as an offshoot of Universiti Teknologi MARA, As an associate member, I am proud to have been involved at the very beginning, developing the module on Integrated Agriculture System under the mentorship of the late Professor Dr. Wan Mohammad Wan Abdul Kadir.